Human cultured cells are capable to incorporate isolated plant mitochondria loaded with exogenous DNA - Klimenko, E.S.; Zaporozhchenko, I.A.; Mileyko, V.A.; Morozkin, E.S.; Koulintchenko, M.V.; Laktionov, P.P.; Konstantinov, Yu.M. (Вiopolymers and Cell, 2012)
Aim. To investigate the possibility of human cultured cells to incorporate isolated mitochondria together with exogenous DNA introduced into organelles. Methods. Two approaches were used for this purpose, fluorescent labelling of mitochondria and/or DNA with subsequent analysis of the cells subjected to incubation by microscopy or by quantitative PCR. Results. We have shown that human cultured cells lines, HeLa and HUVEC, are capable to uptake isolated plant mitochondria and that this process depends on the incubation time and concentration of organelles present in medium. The incorporated mitochondria can serve as vehicles to deliver exogenous DNA into human cells, this DNA is then distributed in different cell compartments. Conclusions. These results are preliminary and need further investigations, including testing the possibility of human cells to incorporate the mitochondria of human or animal origin and creating genetic construction which could provide certain selectivity or stability of the transferred exogenous DNA upon cell uptake of the mitochondria as vectors. Keywords: human cultured cells, DNA-loaded mitochondria, xenotransplantation.